An Analysis of the Pari Passu Doctrine in the Insolvency Law of Uganda - Edrine Setimba (Uganda Christian University, 2024)
This study is about the analysis of the Insolvency law of Uganda in line with the doctrine of Pari passu. “Pari passu” is a Latin word which means equal footing. In Insolvency Law, the Pari passu doctrine states that when there are two competing claims of unsecured creditors and the debtor is pronounced insolvent, the claims or debts from the debtor’s remaining assets are divided on an equal basis amongst the unsecured creditors. In equity, the distribution of the assets of the debtor amongst the creditors is on equitable terms though in pari passu it is on equality terms that the debtor's assets are equally distributed without considering which debt was acquired when and who invested their funds first before the other. This study is challenging such kind of settlement of debts and it's unfair in a way that the one who gave the debtor money first is going to be settled at the same time as those who might have funded the debtor in that month before being pronounced insolvent. This study suggests the change in the law that debts should be settled on a “first in first out” basis because is this equitable and just since funds being issued in a timely manner is of the essence in businesses and the running of companies. This study has research objectives; to find out the law on the doctrine of pari passu during insolvency proceedings, to critique the practice and applicability of the doctrine of pari passu in the Insolvency law of Uganda, to propose the different ways the insolvency laws and the legislation can improve to favour all creditors. The research questions are what is the doctrine of pari passu in insolvency law? What is the law governing the insolvency doctrine of ‘pari passu’? The research uses a desk review method to research the topic and it also helps the researcher to analyze different laws and writings and critically know what other people have written in line with the topic. The research also didn’t limit the scope of the laws to only Ugandan laws but also considered looking into different jurisdictional laws to compare the different approaches to the achievement of writing a well-researched excellent research paper. The researcher at the end gives recommendations and his findings on the research paper by suggesting that some laws need to be amended while practicing insolvency.